2019
DOI: 10.1177/1747954118810505
|View full text |Cite
|
Sign up to set email alerts
|

Workloads placed on adolescent cricket players: A pilot study

Abstract: Cricket players nowadays are faced with increased physical demands, and as a result, it is important to manage their workload, particularly to control and predict risk of injury. While this has been investigated at an elite level, few studies have looked at the workloads placed on adolescent cricket players. The purpose of this study was therefore to determine the workloads placed on school boy cricketers, specifically within a South African context. Twelve male school boy cricketers between the ages of 16 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Between 2018 and 2019, the number of female bilateral Twenty20 (T20) matches International (ODI) matches (short duration, high-intensity protocols) have shown heart rate responses between 136 and 159 beats/min, maximal oxygen uptake measures between 26.92 and 27.00 mL/kg/min and energy expenditures between 2536 and 2765 kJ/h, which is significantly higher than conventionally reported [3,4,22]. These findings are also accurate when compared to real-time matchplay, where heart rate responses of 139-154 beats/min, and 149-167 beats/min have been shown for batters in ODIs and T20 matches respectively [16,20]. Furthermore, simulated ODI century protocols have also been undertaken in a laboratory setting (focusing on longer duration and lower intensities); these investigations identified heart rate responses between 130 and 144 beats/min and an oxygen consumption of 36.70 mL/kg/min [11,24].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Between 2018 and 2019, the number of female bilateral Twenty20 (T20) matches International (ODI) matches (short duration, high-intensity protocols) have shown heart rate responses between 136 and 159 beats/min, maximal oxygen uptake measures between 26.92 and 27.00 mL/kg/min and energy expenditures between 2536 and 2765 kJ/h, which is significantly higher than conventionally reported [3,4,22]. These findings are also accurate when compared to real-time matchplay, where heart rate responses of 139-154 beats/min, and 149-167 beats/min have been shown for batters in ODIs and T20 matches respectively [16,20]. Furthermore, simulated ODI century protocols have also been undertaken in a laboratory setting (focusing on longer duration and lower intensities); these investigations identified heart rate responses between 130 and 144 beats/min and an oxygen consumption of 36.70 mL/kg/min [11,24].…”
Section: Introductionmentioning
confidence: 81%
“…Cricket is a global sport and has grown significantly over the last 20 years, particularly due to the newer, more popular, shorter formats of the game [20]. Traditionally it has been a gentleman's game, dominated by male players but in the past few decades, the women's game has expanded and grown around the world [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…The association between injury risk and bowling workload was investigated in 7 % of articles [22,65,[71][72][73][74][75][76][77][78][79][80][81][82]. 71 % of workload articles investigated bowling workload in adults, and all articles observed that increased workload was related to increased injury risk.…”
Section: Bowling Workload and Injury Riskmentioning
confidence: 99%
“…(50). Therefore, a position-specific training program must be developed to deal with the metabolic demands of all formats of cricket matches (38). This suggests developing conditioning sessions focusing on aerobic endurance using high-intensity interval training methods (Tables 3 and 4).…”
Section: Speed and Agility And Change Of Direction (Cod)mentioning
confidence: 99%
“…This means that strength and conditioning coaches must develop a training program that not only trains a spin bowler for bowling movement patterns but also considers the acute and chronic neuromuscular responses as a result of repeated accelerations, change of direction (COD), and decelerations (50). Therefore, a position-specific training program must be developed to deal with the metabolic demands of all formats of cricket matches (38). This suggests developing conditioning sessions focusing on aerobic endurance using high-intensity interval training methods (Tables 3 and 4).…”
Section: Needs Analysismentioning
confidence: 99%